Tari Tayub Dalam Upacara Sedekah Laut Longkangan Masyarakat Munjungan - Yayuk Retno Wati (Greget, 2012)
Tayub is a genre of folk art in which the movements are still quite simple. This study of Tayub uses a qualitative descriptive method in order to provide a complete picture and present the data obtained about the art of Tayub in a Longkangan ceremony in the village of Munjungan in the district of Trenggalek. The data was collected, classified, and interpreted in order to obtain a complete set of data by using an ethno-choreological approach. Tayub is used as a part of the Longkangan ceremony in the village of Munjungan. In connection with the function of Tayub in a fertility ritual, it is performed as part of the Longkangan sea-offering ceremony. This ceremony is surrounded by numerous conditions and requirements, such as the time of the ceremony which must be in the month of Dulkaidah or Longkang. The Tayub performance takes place on the Blado Munjangan coast. Tayub is an essential part of the Longkangan ritual and the local community believe that if Tayub is not performed, danger may strike. The Tayub performance holds an important position in this ceremony as an expression of the community about their traditional beliefs. Keywords : Tayub, Longkangan, Ceremony.